A6.3 Patients with bronchiectasis, with or without rheumatoid arthritis, have an elevated anti-citrullinated peptide antibodies (ACPA) response. (31st January 2014) - Quirke, Anne-Marie; Perry, Elizabeth; Kelly, Clive; de-Soyza, Anthony; Eggleton, Paul; Hutchinson, David; Venables, Patrick
Abstract : Background and Objectives: ACPA, particularly antibodies to citrullinated enolase and vimentin, are associated with smoking in patients with rheumatoid arthritis (RA). There is increasing evidence that these links are due to expression of citrullinated proteins in the lungs of smokers. Whether this is a direct effect of smoking or inflammation is presently poorly understood. Bronchiectasis, a strong risk factor for RA, tends to occur in non-smokers, and can therefore be used to examine the role of inflammation in generating an ACPA response independent of smoking. Materials and Methods: This multi-centre study included 53 patients with HRCT proven bronchiectasis and RA, 50 patients with RA without lung disease, 124 bronchiectasis without RA and 87 asthma patients as controls. Serum samples were analysed for ACPAs using anti-CCP (2 nd generation assay) and in-house ELISA's were used to measure fine specificities to citrullinated α-enolase (CEP-1), citrullinated vimentin (cVim) and fibrinogen (cFib) together with their arginine-containing control peptides. Smoking history was detailed for all patients. Results: Comparing the RA/bronchiectasis and the RA patients without lung disease, anti-CCP antibodies were more frequently positive (87% vs 48%) and titre significantly greater (p<0.0001) in the RA/bronchiectasis group, despite a lower frequency of smoking (42% vs 58%). The frequency and titre were also increased in the RA/bronchiectasis group for anti CEP-1 (60% vs 24%; p < 0.001), cVim (34% vs 11%; p < 0.001) and anti-cFib (38% vs 18%; p = 012). Comparing the bronchiectasis with asthma groups, none of who had RA, 5% vs 2% had anti-CCP, 9% vs 2% had anti CEP-1 and none were anti-cVim or anti-cFib positive. However, the increased ACPA response in bronchiectasis vs asthma was significant for anti-CEP-1 (p < 0.001). Testing with REP-1, the arginine-containing control peptide for enolase, showed that the response in the bronchiectasis patients was not citrulline-specific. Conclusions: We have demonstrated that despite a low prevalence of smokers, RA/bronchiectasis patients have increased anti-CCP antibodies and an ACPA fine specificity profile similar to that previously shown in RA and smoking (anti-CEP-1 and anti-cVIM). Additionally we identified significantly elevated levels of anti-CEP-1 in the bronchiectatis patients, though unlike in the RA patients, the response was not citrulline-specific, similar to that previously reported for periodontitis. This indicates that the lung may be an initiating site for immunity to RA autoantigens due to inflammation independent of smoking.